National specialization and diversification in the bioeconomy: Insights from biobased technologies in chemical and pharmaceutical sectors - Fischer, Lennart; Losacker, Sebastian; Wydra, Sven; Justus Liebig University Giessen (My University, 2024)
Facilitating the transformation of innovation systems is a vital endeavor within the global quest to diminish the detrimental environmental consequences of economic activities. Against this background, scholars and policymakers emphasize the potentials of a societal transition towards a ‘bioeconomy’. In this paper, we study the technological specialization of countries in biobased technologies relating to chemicals and pharmaceuticals, which are key constituents for a future bioeconomy. By identifying these technologies in patent and publication data, we analyse specialization and diversification processes for 15 countries from 1997 to 2019. We find that countries that already had a relative advantage in biobased technologies are more likely to develop new specializations in technologies that relate to the bioeconomy. Beyond that, countries' specialization in biobased technologies varies between basic research (scientific publications) and applied research (patents). Our study also shows that greater technological complexity tends to limit specialization in biobased publications, highlighting the need for targeted policy interventions supporting the bioeconomy.
Keywords: ddc:910